Testing Unemployment Persistence in Central and Eastern European Countries - Gozgor, Giray (International Journal of Economics and Financial Issues, 2013)
This study investigates whether stochastic properties of the unemployment rate in ten Central and Eastern European Countries (CEE) countries: Bulgaria, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia and Slovenia can be explained by the non-accelerating inflation rate of unemployment or the hysteresis hypotheses. We primarily show the cross-sectional dependence in unemployment rates, and then apply panel-based unit root tests that take cross-section dependence into account. The empirical findings indicate that there is no mean-reverting process in unemployment rates for ten CEE countries. Thus the results provide evidences for validity of the hysteresis hypothesis—unemployment persistence—in related CEE countries. Keywords: Unemployment persistence; Panel-based unit root tests; Cross-section dependence JEL Classification: C23; J64